Pengenalan Tumbuhan Obat Kayu Putih (Melaleuca cajuputi) kepada Siswa melalui Eduwisata di Kebun Raya Universitas Halu Oleo - Nurnaningsih Hamzah; Nurhayati Hadjar; Abigael Kabe; Abdul Sakti; Wiwin Rahmawati Nurdin; Sarwinda Intan Putri; Lade Ahmaliun; Dewi Fitriani; Sahindomi Bana; Wa Ode Hastiani Fahidu (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2025)
The objective of this community service activity was to improve the understanding of fifth-grade students at SD 92 Kendari regarding the medicinal plant Melaleuca cajuputi through an ecotourism education programme at the Halu Oleo University Botanical Garden. The methods used included presenting material on the benefits of medicinal plants, particularly cajuput, as well as direct observation of cajuput trees in the botanical garden. The activity also involved explanations from the botanical garden managers regarding biodiversity and the importance of preserving medicinal plants. The results of this activity showed a significant increase in students' knowledge of the medical and ecological benefits of cajuput. Before the activity, most students only knew white wood as a mild medicinal product, but after participating in the activity, 85% of students demonstrated a deeper understanding of the medical benefits of white wood, including its antimicrobial, anti-inflammatory, and analgesic properties. Additionally, students developed an awareness of the importance of preserving medicinal plants and biodiversity. This eco-tourism-based educational activity proved effective in increasing students' interest in environmental conservation and introducing them to sustainability concepts. These findings underscore the importance of developing botanical gardens as educational centres that can support environmental conservation and the preservation of medicinal plants for a better future.